Symptoms and longitudinal changes in lung function in young seasonal grain handlers. Issue 9 (September 1986) - James, A L; Cookson, W O; Buters, G; Lewis, S; Ryan, G; Hockey, R; Musk, A W
Abstract : A total of 119 seasonal grain handlers (mean age 23) were assessed before and towards the end (mean work period 18 days) of the 1983 Western Australian grain harvest to determine if respiratory symptoms that occur with exposure to grain dust are associated with changes in ventilatory capacity or non-specific bronchial reactivity to methacholine. Eighteen per cent of subjects had wheeze, breathlessness, or chest tightness and 18% had cough or sputum production at work. Subjects complaining of wheeze, chest tightness, or breathlessness at work had a significantly greater decline in FEV1 than subjects who did not experience these symptoms (p less than 0.05). Symptoms were not associated with changes in bronchial reactivity. In young grain handlers who develop respiratory symptoms on short term exposure to grain dust changes in FEV1 but not in non-specific bronchial reactivity have been demonstrated.